A galáxia de Gutenberg: possibilidades da leitura digital e seu uso no contexto universitário - Nascimento, Misael Batista do (2019)
This research investigates the easy and difficult aspects of using digital books as an incentive to read in the university context, pointing out indicators that contribute to the use of digital books in this environment. It covers a contemporary theme, related to the research lines of the post-graduation program of Education, Philosophy and Theology Center (CEFT) of Mackenzie Presbyterian University and it covers the areas of Education and Technology (digital languages, new media and the Internet, teaching/learning and new technologies). To perform this research, it was required the use of hypothetical-deductive method, indirect (bibliography) and direct documentation (questionnaire). The theoretical framework includes interdisciplinarity, with text support on philosophy, anthropology, communication, hermeneutics, learning, language, writing and reading, history and book design, technologies, digital culture and digital books. The result of this work makes it possible to affirm that there are singularities in the experience of reading digital books, as well as resources in these same books, which can encourage reading in the university context. The university student gradually incorporates the reading of the digital book, but still has difficulty in using all its resources. In addition, in the university context, the reading of digital books is little encouraged by professors.